Pengaruh Profitabilitas, Ukuran Perusahaan, dan Reputasi KAP Terhadap Audit Report Lag - Silvia Gunawan; Yosevin Afelia; Santy Setiawan (Universitas Kristen Maranatha, 2022)
Timeliness in auditing is one of the characteristics required so that financial information can be said to be useful. The purpose of this study was to determine the effect of profitability, company size, and reputation of the Public Accounting Firm on audit report lag. The sample of this research is the food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2018-2020. There are 22 companies that meet the predetermined criteria, so that a total of 66 observations are collected. Hypothesis testing using a logistic regression test. The results of the Wald test revealed that profitability has a negative effect on audit report lag, meaning that companies that are able to produce high levels of profitability will take a shorter time in the audit process. While the size of the company and the reputation of the Public Accounting Firm do not affect the audit report lag because they are not decisive factors in issuing financial reports on a timely basis.Keywords: Profitability, Company Size, Reputation of the Public Accounting Firm (KAP), and Audit Report Lag